Processing And Pelletizing Of High Grade Malaysian Iron Ore - Bain, Siti Nurba'inah Mohd (Universiti Sains Malaysia, 2017)
Research was conducted on the high grade iron ore was obtained from Honest Sam Development. Sdn. Bhd, Chaah, Johor, Malaysia. The purpose of this study to investigate the chemical composition element and impurities present in this sample, the pelletization technique of concentrate before it was fed to the blast furnace with different binders and amount dosage and mechanical strength tests have carried out. The experimental and technical procedures for high grade iron ore outlined and the pelletizing operations and processes discussed. The result of the tests was presented. Two organic binders, Peridur 350 and Peridur 315 were studied and the effects towards the physical and mechanical properties of the pellets. The results obtained shows that the optimum effect of high dosage of binder 0.1% wt of binder with fired condition are stronger compared to the others with different amount of dosage binder and moisture content condition. From the mineral characterization and iron ore beneficiation, shows that almost 62% of Fe present in the sample while major impurity, silica almost 5%. Therefore, the sample was found to be a high grade iron ore. The result of wet compression strength was lower than that proposed by industry. Pelletizing of iron ore is necessary to avoid some loss of weight of iron ore in powder form during shipping to steel industry and while handling. Result for pellets made of 0.1% wt using Peridur 350 as a binder give out an excellent result for fired and dry compressive strength. Peridur 315 give minimum or can be considered results. Combination of both binder with amount 0.1% shows the excellent results by achieving good physical and mechanical properties of pellet.